New Drivers of Division Urbanisation and Spatial Inequality in Africa and Asia - Wang, Ya Ping.; Kintrea, Keith; Everatt, David; Kundu, Debolina; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book provides recent trends of urbanization and inequality in Africa and Asia. It addresses the inequality challenges of urbanization and large-scale rural-to-urban migration. It answers questions around socio-economic and spatial inequalities and how serious those are in cities in Africa and Asia under 21st-century urbanization. Chapters demonstrate how the old neighborhood division in cities based on race, ethnicity, religion, apartheid, tribes, caste and migrant are replaced by social class through sorting in the housing market. The analyses go beyond the normal income inequality consideration and take a broader perspective on inequality by considering these issues at the neighborhood level to reveal the new spatial divisions in cities. As such, it is essential reading for academics and students in urban studies, sociology, geography, planning, and policymakers working on urban development around the world.
Chapter 1. Introduction (Ya Ping Wang) -- Chapter 2. Urban Inequality and Socio-Spatial Segregation (Keith Kintrea) -- Chapter 3. Urbanisation and Neighbourhood Inequality in the Global South (Ya Ping Wang) -- Chapter 4. Urban Education and Neighbourhood Inequality (Yulia Nesterova) -- Chapter 5. Neighbourhood Effects on Health in Urban Areas of Developing Countries (Ramjee Bhandari) -- Chapter 6. Continuity or Change? Racial Segregation in Cape Town (Justin Visagie) -- Chapter 7. Measuring Local Exposure to Economic Inequality in the City of Johannesburg (Halfdan Lynge) -- Chapter 8. Socio-spatial Inequality in Urban Neighbourhoods in Johannesburg: Place, Belonging and Agency (Caryn Abrahams) -- Chapter 9. Urban Expansion and Neighbourhood Inequality in Kigali (Gilbert Nduwayezu) -- Chapter 10. Neighbourhood Inequalities and Access to Housing, Amenities and Services: A Comparative Analysis of Delhi and Madurai (Debolina Kundu) -- Chapter 11. Neighbourhood Inequalities and Challenges to Urban Planning in Dhaka (Shilpi Roy) -- Chapter 12. Urbanisation and Neighbourhood Diversification in Chongqing (Yunxia Liu) -- Chapter 13. Spatial Inequality in Manila: A Case Study of (Un)caring Urban Ethics in Jaime Cardinal Sin Village and the Manila North Cemetery (Ryan Randle B. Rivera) -- Chapter 14. Income, Employment and Housing Inequalities in Asian and African Cities (Sohail Ahmad).
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sociology, Urban; Human geography; Sustainability; Urban Sociology; Human Geography; Sustainability